Capsular types of Klebsiella pneumoniae revisited by wzc sequencing. - Yi-Jiun Pan; Tzu-Lung Lin; Yen-Hua Chen; Chun-Ru Hsu; Pei-Fang Hsieh; Meng-Chuan Wu; Jin-Town Wang (PLoS ONE, 2013)
Capsule is an important virulence factor in bacteria. A total of 78 capsular types have been identified in Klebsiella pneumoniae. However, there are limitations in current typing methods. We report here the development of a new genotyping method based on amplification of the variable regions of the wzc gene. Fragments corresponding to the variable region of wzc were amplified and sequenced from 76 documented capsular types of reference or clinical strains. The remaining two capsular types (reference strains K15 and K50) lacked amplifiable wzc genes and were proven to be acapsular. Strains with the same capsular type exhibited ≧94% DNA sequence identity across the variable region (CD1-VR2-CD2) of wzc. Strains with distinct K types exhibited <80% DNA sequence identity across this region, with the exception of three pairs of strains: K22/K37, K9/K45, and K52/K79. Strains K22 and K37 shared identical capsular polysaccharide synthesis (cps) genes except for one gene with a difference at a single base which resulted in frameshift mutation. The wzc sequences of K9 and K45 exhibited high DNA sequence similarity but possessed different genes in their cps clusters. K52 and K79 exhibited 89% wzc DNA sequence identity but were readily distinguished from each other at the DNA level; in contrast, strains with the same capsular type as K52 exhibited 100% wzc sequence identity. A total of 29 strains from patients with bacteremia were typed by the wzc system. wzc DNA sequences confirmed the documented capsular type for twenty-eight of these clinical isolates; the remaining strain likely represents a new capsular type. Thus, the wzc genotyping system is a simple and useful method for capsular typing of K. pneumoniae.